The smartphone technology acceptance among Malaysian young adults - Mad Lazim, Halim; Sasitharan, , (2014)
Smartphone technology can be characterized as multi-function device that helps people to manage their task. This study is being emphasized because there is no legitimate answer in Malaysian context whether perceived usefulness had contributed an impact on smartphone technology acceptance. Therefore, there is a need to explore how perceived usefulness affect smartphone technology acceptance among Malaysian young adults. This study was conducted using (TAM) model to capture detailed view about perceived usefulness and the relationship with smartphone technology acceptance among Malaysian young adults. The findings of this study confirmed that perceived usefulness drives the smartphone technology acceptance among Malaysian young adults and it cannot be denied that the advanced features of smartphone technology had influenced Malaysian young adults to possess smartphone technology and make use of it for their personal tasks.